Patient Expectations of Assigned Treatments Impact Strength of Randomised Control Trials - Truzoli, Roberto; Reed, Phil; Osborne, Lisa A. (Frontiers in Medicine, 2021)
Patient engagement with treatments potentially poses problems for interpreting the results and meaning of Randomised Control Trials (RCTs). If a patient is assigned to a treatment that does, or does not, match their expectations, and this impacts their motivation to engage with that treatment, it will affect the distribution of outcomes. In turn, this will impact the obtained power and error rates of RCTs. Simple Monte Carlo simulations demonstrate that these patient variables affect sample variance, and sample kurtoses. These effects reduce the power of RCTs, and may lead to false negatives, even when the randomisation process works, and equally distributes those with positive and negative views about a treatment to an arm.